2014
DOI: 10.1111/jne.12149
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Lesion Increases Oestrogen Receptor α Expression in the Intact Side of the Ventromedial Hypothalamic Nucleus in Ovariectomised Rats

Abstract: To determine the relationship between the right and left sides of the ventrolateral ventromedial hypothalamic nucleus (vlVMN) in regulating the expression of oestrogen receptor (ER)α, the unilateral vlVMN was lesioned and the number of ERα-immunoreactive cells and the ERα mRNA level in the intact side of the vlVMN and arcuate nucleus (ARC) were measured in ovariectomised rats. Twenty-four hours after lesioning, brain samples were collected for analysis of ERα expression by immunohistochemistry and the real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…A behavioral experiment using a toxin specific to serotonergic neurons has shown that the target of lordosis-inhibiting 5-HT-positive axons is the VMN [14]. However, serotonergic neurons in the VMN may not be involved in the regulation of ER␣ expression, although neural inputs to the VMN have been reported to control ER␣ expression [23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A behavioral experiment using a toxin specific to serotonergic neurons has shown that the target of lordosis-inhibiting 5-HT-positive axons is the VMN [14]. However, serotonergic neurons in the VMN may not be involved in the regulation of ER␣ expression, although neural inputs to the VMN have been reported to control ER␣ expression [23].…”
Section: Discussionmentioning
confidence: 98%
“…Photomicrographic digital images were taken from two sections for the AVPV or three sections for the vlVMN and ARCN for each rat (corresponding to rat brain atlas of [19]) using a Digital Microscope Camera (DP72, Olympus, Tokyo). Counting areas for the vlVMN and ARCN were chosen from three sections located 2.28-2.76 mm posterior from the bregma that contain the rostral part of vlVMN, according to the previous report [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation